Determinants of malaria incidence : Analysis of lifestyle and breeding place - Azwar, Muhammad; Wulandari, Ambar; Nursiah, Andi; Widiastuty, Lilis (Universitas Islam Negeri Alauddin Makassar, 2024)
Malaria is an infectious disease caused by the Plasmodium parasite, transmitted through the bites of infected Anopheles mosquitoes. This disease remains a significant public health problem, especially in tropical and subtropical regions. This study aims to identify the factors associated with malaria incidence in the working area of the Tanah Merah Health Center, Mandobo District, Boven Digoel Regency, Papua Province. The study was conducted in the Mandobo District. This type of research is observational with a cross-sectional study design. The population in this study comprised all patients who visited the Tanah Merah Health Center, while the sample was determined using simple random sampling, resulting in a sample of 140 respondents. The data analysis used was the Chi-square test. The results showed that the factors contributing to the incidence of malaria in the working area of the Tanah Merah Health Center, Mandobo District, Boven Digoel Regency, were the habit of being outside at night (p=0.000), the use of bed nets (p=0.001), mosquito breeding place (p=0.000), and the use of mosquito repellents (p=0.004). Malaria control is expected to involve community participation in environmental modification aimed at reducing mosquito breeding habitats, such as improving drainage systems in collaboration with local governments, filling in unused holes or ponds, and marshlands to prevent them from becoming mosquito breeding sites